Az óvodáztatási támogatásról: Egy feltételekhez kötött készpénz-támogatási program értékelése - Gábor Kertesi; Gábor Kézdi (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2012)
– This paper aims at estimating the effect of the kindergarten allowance program (a conditional cash transfer program organized by the government) introduced in Hungary in January 2009. We use institutional kindergarten data and municipality-level demographic data spanning ten years (2001 through 2010), as well as administrative data from the program in 2009 and 2010. We estimate the effect of the program on the kindergarten attendance of children of age 3 and 4 in years 2009 and 2010. Our results indicate that the program had some modest positive effects. We point out several problems of program implementation that may be responsible for the modest effects. In particular, the estimated effects are largest in areas where kindergarten capacities are abundant relative to potential demand, and smaller where capacity constraints may be binding.
Keywords: I20; I38; 330; kindergarten; conditional cash transfer; program evaluation; Hungary; Bildungspolitik; Kinderbetreuungseinrichtung; Wirkungsanalyse; Ungarn